2017
DOI: 10.1002/jcb.26219
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Peroxide Stimulates Exosomal Cathepsin B Regulation of the Receptor for Advanced Glycation End‐Products (RAGE)

Abstract: Exosomes are nano-sized vesicles that are secreted into the extracellular environment. These vesicles contain various biological effector molecules that can regulate intracellular signaling pathways in recipient cells. The aim of this study was to examine a correlation between exosomal cathepsin B activity and the receptor for advanced glycation end-products (RAGE). Type 1 alveolar epithelial (R3/1) cells were treated with or without hydrogen peroxide and exosomes isolated from the cell conditioned media were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…RAGE is a 35 kilodalton transmembrane receptor of the immunoglobulin superfamily, and it is widely expressed, predominantly in the lungs [31,32]. Experimental data indicated that RAGE is mainly presented on vascular smooth muscle cells [33], airway smooth muscle cells (ASM), endothelial cells and pulmonary macrophages [34]. Additionally, there is clinical evidence that neutrophilic airway inflammation in COPD and asthma is associated with reduced soluble RAGE [35].…”
Section: Discussionmentioning
confidence: 99%
“…RAGE is a 35 kilodalton transmembrane receptor of the immunoglobulin superfamily, and it is widely expressed, predominantly in the lungs [31,32]. Experimental data indicated that RAGE is mainly presented on vascular smooth muscle cells [33], airway smooth muscle cells (ASM), endothelial cells and pulmonary macrophages [34]. Additionally, there is clinical evidence that neutrophilic airway inflammation in COPD and asthma is associated with reduced soluble RAGE [35].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous work has also shown a role for RAGE in response to vesicle-mediated protein transport in that exosomes obtained from cells treated with H 2 O 2 promote RAGE expression in alveolar epithelial cells. [35] This suggests that RAGE may play a role in directing the content and formation of exosomes in the alveolus.…”
Section: Discussionmentioning
confidence: 99%
“…We have summarized the key characteristics of the studies in Table 1. Of these studies, nine (30%) listed nurses as first authors (Cybulska et al, 2019; Downs et al, 2018; Ferranti et al, 2017; Gregory et al, 2013; Heitkemper et al, 2016; Lyon et al, 2018; Menzies et al, 2020; Starkweather et al, 2017; Thompson et al, 2019). Additionally, one research abstract (3.3%) listed nurse authors as both first and senior author (Faucher et al, 2019), and one study (3.3%) included a nurse as senior, but not first, author (Chen et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Metabolomics studies identified for this review were published in a wide array of biology/biochemistry, clinical, specialty, and nursing journals. Seven papers (23.3%) were published in biology/biochemistry journals (Alvarez et al, 2017; Chen et al, 2018, 2019; Downs et al, 2018; Gregory et al, 2013; Irving et al, 2015; Wang et al, 2018b). Eight papers (26.7%) were published in clinical journals (Cybulska et al, 2019; Hollister et al, 2019; Lu et al, 2016; Mapstone et al, 2017; Mayers et al, 2014; Menzies et al, 2020; Wang et al, 2018a, 2019).…”
Section: Resultsmentioning
confidence: 99%